Distributional effects of the COVID-19 lockdown - Marius Clemens; Maik Heinemann (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
A two-sector incomplete markets model with heterogeneous agents can be used to study the distributional effects of the COVID-19 lockdown. While negative aggregate welfare effects of the lockdown are unavoidable, the size of aggregate welfare effects as well as the distribution of the welfare effects across agents turn out to depend on the specific economic environment of the affected economy as well as the response of the government to the shock. We use the model to simulate the lockdown effects based on a calibration to German data. First, we find that without state aid and limited access to international financial markets especially poor household suffer large welfare losses, while wealthy house- hold could even benefit from the lockdown. Second, a state aid program reduces large parts of the welfare losses of workers across all income groups in the affected sectors by forcing loss sharing with agents working in the non-affected sector. However, wealthy households no matter in which sector still benefit more than the average household. Third, access to international financial markets is key to shift relative welfare gains from superrich to poorer households in both sectors. Once the country is able to borrow internationally, the benefit for superrich diminishes. Our results implicate that countries with rather limited access to financial markets and less stable government budget positions will suffer higher welfare losses and increases in inequality.
Keywords: D31; E21; E62; I14; 330; COVID-19; Income and Wealth Inequality; Heterogeneous Agents; Fiscal Policy